СУЩЕСТВУЕТ ЛИ ЭКОЛОГИЧЕСКАЯ ЭТИКА - Rolston, Holmes, 1932-2025, author; Progress Publishers, publisher (Colorado State University. Libraries, 1990)
An ecological ethic is puzzling in its mixture of science and ethics. A) In secondary ecological ethics, we distinguish a proximate moral ought, ecologically informed, operating through natural law, but which is preceded by an antecedent moral ought that is classical. Injunctions to recycle are of this kind. B) in primary ecological ethics, ecosystemic evaluation has informed even the antecedent moral ought, and the descriptive and prescriptive arise together. Injunctions to maximize the beauty, integrity, and stability of the ecosystem are of this kind.
Is there an ecological ethic?
Text in Russian.
Keywords: conservation; ecosystems; stewardship; environmental ethics; ecological ethics; ecology; natural law; moral principles